Sulfamethoxazole-trimethoprim plus rifampicin combination therapy for methicillin-resistant Staphylococcus aureus infection: An in vitro study - Masaki Nakamura; Yoshinori Tomoda; Masahiro Kobayashi; Hideaki Hanaki; Yuhsaku Kanoh (PLoS ONE, 2025)
Methicillin-resistant Staphylococcus aureus (MRSA) is highly drug-resistant. The current Japanese guidelines (2019 edition) for managing and treating MRSA infections mention alternative anti-MRSA agents, including sulfamethoxazole-trimethoprim (ST) and rifampicin (RFP). Both ST and RFP are oral drugs and are expected to be effective alternatives to anti-MRSA drugs in clinical cases where anti-MRSA drugs are not indicated. Although guidelines for treating MRSA infections describe the efficacy of ST-RFP combination therapy and although it is used in clinical practice, only a limited number of in vitro studies have demonstrated its efficacy in pharmacokinetic/pharmacodynamic models. This study aimed to investigate the efficacy of the combination therapy of ST-RFP against MRSA in some in vitro models, including a pharmacokinetic/pharmacodynamic model. The MRSA strains obtained were subjected to antibiotic susceptibility tests. A checkerboard assay for drug combination synergy of ST-RFP was performed. Furthermore, a chemostat model was used to validate the combination therapy of ST-RFP as an in vitro pharmacokinetic/pharmacodynamic model. Viable cell counts and antibiotic concentrations were measured. The checkerboard assay showed that the ST-RFP combination had an additive effect on all strains (the lowest fractional inhibitory concentration index ranged from 0.63 to 1.00). The in vitro chemostat model demonstrated the usefulness of the combination of ST-RFP against MRSA, especially in ST-resistant strains. Regrowth of MRSA was observed in RFP monotherapy but not in the ST-RFP combination therapy. This study demonstrated the potential effectiveness of the ST-RFP combination against ST-resistant MRSA, providing important foundational data that may support future clinical investigations.